(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2018)
The aim of this article is to present unemployment insurance for artisanal professional fishermen from a dual perspective: environmental policy to protect species and social policy to guarantee income to the specially insured during the period in which they are unable to carry out their professional activity. The relevant legislation is analyzed in order to build a theoretical and pragmatic framework of the requirements for granting the benefit. The study concludes by revealing that the transfer of the granting of unemployment insurance benefits as a result of the closed season to the National Social Security Institute is one of the Federal Government’s measures aimed at subjecting this public social security policy to strict state control.